The unusually diverse mortality patterns in the Pacific region during the 1918–21 influenza pandemic: reflections at the pandemic's centenary. Issue 10 (October 2018) - Shanks, G Dennis; Wilson, Nick; Kippen, Rebecca; Brundage, John F
Summary: The 1918–21 influenza pandemic was the most lethal natural event in recent history. In the Pacific region, the pandemic's effects varied greatly across different populations and settings. In this region, the pandemic's lethal effects extended over 3 years, from November, 1918, in New Zealand to as late as July, 1921, in New Caledonia. Although a single virus strain probably affected all the islands, mortality varied from less than 0·1% in Tasmania, to 22% in Western Samoa. The varied expressions of the pandemic across the islands reflected the nature and timing of past influenza epidemics, degrees of social isolation, ethnicity and sex-related effects, and the likelihood of exposures to pathogenic respiratory bacteria during influenza illnesses. The high case-fatality rate associated with this pandemic seems unlikely to recur in future influenza pandemics; however, understanding the critical determinants of the mass mortality associated with the 1918–21 pandemic is essential to prepare for future pandemics.